2016
DOI: 10.1057/s41286-016-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

Becoming an airline passenger: Body, luggage, and documents

Abstract: This paper deploys a relational-material approach for tracing the assembly of passengers as they move through airports and use its series of passage points. While many studies analyse airport mobility and passengers' experiences, few do so with the question of subjectivity as their main theoretical focus. Rather than treating subjectivity as an epiphenomenon or alternatively as a myriad of spatio-sensual experiences, we treat the subjectivity of airline passengers as a product and an achievement: a work of ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Air travel is highly differentiated, bodies are funneled into different spaces according to class, nationality, perceived threat, etc. and bodies are expected to be docile, to obey rules about how to behave, to be open to scrutiny and surveillance (Adey, 2008;Shilon and Shamir, 2016). Power relations are absolute here.…”
Section: Bodily Intensities and Flying While Fatmentioning
confidence: 99%
“…Air travel is highly differentiated, bodies are funneled into different spaces according to class, nationality, perceived threat, etc. and bodies are expected to be docile, to obey rules about how to behave, to be open to scrutiny and surveillance (Adey, 2008;Shilon and Shamir, 2016). Power relations are absolute here.…”
Section: Bodily Intensities and Flying While Fatmentioning
confidence: 99%
“…Disparities in travel freedom are also manifested at airports and other ports of entry. Passengers with lower-value passports face stricter questioning and are more likely to be denied entry or selected for additional inspection (Neumayer 2006;Salter 2006;Shilon and Shamir 2016). In many countries, border crossings have separate lines for different categories of passengers.…”
Section: A Global Hierarchy Of Travel Freedommentioning
confidence: 99%
“…Existing studies have shown that travelers attach status implications to differences in travel competence associated with experience, ethnicity, or spending power. Frequent air travelers show their high status by moving through the airport with speed, confidence, and ease (Shilon and Shamir 2016). Passengers who are ethnically profiled for extra questioning experience the different treatment as humiliating (Hasisi, Margalioth, and Orgad 2012).…”
Section: International Travel Freedom: a Status Perspectivementioning
confidence: 99%
“…From the (aero)mobilities perspective, 3 studies of passenger behaviour and experience have revealed the changeable and ambiguous nature of passengers and the multiplicity of their practices socio-material interactions and experiences within the context of travelling (Cresswell 2006;Adey 2009;Kesselring 2009;Lassen 2009;Shilon and Shamir 2016). For instance, different people make sense of the airport space and inhabit it differently (e.g.…”
Section: Situated Passenger Flows and Practicesmentioning
confidence: 99%